Potential infection risk assessment of improper bioaerosol experiment operation in one BSL-3 laboratory based on the improved Wells-Riley method. (15th August 2021) - Liu, Zhijian; Zhuang, Wenbin; Hu, Xiaoqi; Zhao, Zhiheng; Rong, Rui; Li, Jinsong; Li, Na; Ding, Wenjun
Abstract: Laboratory-acquired infection caused by improper operation in the course of experimental process is frequently reported, so the exposure risk study of biosafety laboratory has become a top priority. In this study, the infection risk of bioaerosols under three typical improper operations was investigated by means of Computational Fluid Dynamics (CFD) method coupled with Wells-Riley equation based on one typical BSL-3 laboratory bioaerosol releasing experiment. Filed measurement of concentrations of two bioaerosols ( Serratia marcescens and phage ΦX174) were used to verify the accuracy of the CFD model. Combined with air-age isosurface map, the potential infection risk and time disinfection law were explored in detail. The results showed that the air recirculation zone of the laboratory is mainly located near the experimental equipments, and the bioaerosol removal efficiency in regions above 1.5 m is low. The risk of infection in different regions varied by more than 20 times. In addition, the potential exposure per minute was higher at the beginning of the leak, and the risk value was maintained at about 1%/min after 4 min. These findings provide some guidance suggestions for disinfection procedures that the first is to avoid the initial exposure of leakage, and the second is to grasp high-risk targeted disinfection location. Highlights: Bioaerosol infection risk of improper operation in a BSL-3 laboratory was evaluated. High-risk regions combined with air-age isosurface map in a BSL-3 laboratory was explored. Time distribution trend of infection probability in the high-risk region was calculated. Some reasonable guidance suggestions for disinfection time schedule were proposed.